Evaluasi Pasca Program Pembelajaran Khusus Kepala Kabupaten di Kedeputian Wilayah Papua & Papua Barat Tahun 2021 dengan Model Kirkpatrick Level 3 - Win Dharlan Siallagan; Nurullah Hasibuan; Firman Adrian; Chandra Nurcahyo (Jurnal Jaminan Kesehatan Nasional, 2022)
One way to create competent and professional human resources is through training designed according to the organization's needs and carried out comprehensively and continuously. BPJS Kesehatan, through Corporate University, plays a role in developing employees according to organizational needs in the form of a Learning Program. Corporate University evaluates all learning programs. This study aims to analyze the results of the evaluation after the Special Learning Program for District Heads in the Ministry of Papua and West Papua Regions in 2021 to provide an overview of the extent of the implementation of the learning program results, changes in participant behavior in the workplace, and provide proposed actions that need to be taken to improve the learning program in the future. This research uses descriptive methods with quantitative and qualitative approaches. Based on the results of the evaluation, it is known that the Competency Score for each competency is still below the target value of 5 on a scale of 6, namely the Building Trust competency with a score of 4.97; impact & influence competency with a score of 4.93 and Strive for Excellence competency with a score of 4.79. The results of the evaluation found that there were 13 behavioral indicators (68.4%) that had scores below the target value. The implementation of the results of the learning program still needs to have a significant influence on increasing the competence of participants. The learning program still has not changed participants’ behavior by the behavioral indicators of each competency that is the target of the learning program. The availability of facilities and infrastructure in the work environment still needs to be improved. Other factors that need attention are knowledge and skills, superior support, and self-motivation. The knowledge and skills that need to be improved are Communication Skills, Negotiation Skills, and regulations related to Local Government. External factors affecting performance are geography and security, family support, and cooperation with external parties.